(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
This study looks at debt burden among college graduates and compares it to previous research by taking institutional and state variables into consideration. Using a combination of national datasets using zero-one inflated beta regression, we uncover a number of interesting trends. First, family income and college experiences have a substantial impact on the chance of having no debt and the degree of debt burden. Second, graduates of private colleges are more likely than graduates of public universities to be in debt. Finally, although state funding of merit-based aid programs helps to lower student debt, when the "Georgia effect" is taken into account, the advantage is lost. On the roles that institutions and the government may play in reducing student debt, conclusions and suggestions are provided. Grants currently account for just 52 percent of total undergraduate financial aid, with the remaining 39 percent coming from government and commercial loans. As a result of these changes in federal and state regulations, there has been a large increase in student borrowing. Between 1995– 96 and 2007–08, the percentage of undergraduates borrowing increased from 37.8% to 46.2 percent at public four-year colleges and from 48.5 percent to 58.9% at private, nonprofit four-year schools.